2012
DOI: 10.7903/cmr.9693
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of a Global Mindset: A Mixed Method Analysis of Indian, Chinese and Japanese Managers

Abstract: There is a growing literature pointing to the importance of global organizations having managers with global mindsets. However, some theoretical issues and contradictory research findings require attention, especially in the case of non-Western contexts. The aim of this article is to examine the extent to which current understandings about the antecedents of global mindsets apply to Indian, Chinese and Japanese organizations. Employing a quantitatively driven mixed method approach, survey data from 504 manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(62 reference statements)
0
3
0
1
Order By: Relevance
“…Entrepreneurs have the ability to identify new market opportunities, contribute to business formation, and reverse the effect of brain drain. Yet, it can be noticed that literature on entrepreneurship and economic growth focuses mostly on the U.S. Not only is there lack of literature on Indian entrepreneurs in Gulf countries, but there is also an absence of examination of innate traits and competencies that contribute to one's entrepreneurial orientation, that develop as by-products of the migrant's upbringing, social interaction, economic environment, and psychological state (Ananthram, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Entrepreneurs have the ability to identify new market opportunities, contribute to business formation, and reverse the effect of brain drain. Yet, it can be noticed that literature on entrepreneurship and economic growth focuses mostly on the U.S. Not only is there lack of literature on Indian entrepreneurs in Gulf countries, but there is also an absence of examination of innate traits and competencies that contribute to one's entrepreneurial orientation, that develop as by-products of the migrant's upbringing, social interaction, economic environment, and psychological state (Ananthram, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Organisational factors Organisational characteristics Ananthram et al (2010), Cole and Konyu-Fogel (2011), Dekker (2013), Felício et al (2013), Felício et al (2012), Kobrin (1994) Characteristics of a company including organisation's location, size, and industry Organisational managers' characteristics Ananthram et al (2012), Arora et al (2004), Dekker (2013), Gupta and Govindarajan (2002), Levy (2005), March (2013), Massingham (2013), Nielsen (2014), Nummela et al (2004), Paul (2000), Ransom (2007), Story et al (2014) Factors that refer to management structure, manager's characteristics, and leadership role Organisational practises Ananthram et al (2010), Arora et al (2004), Dekker et al (2005), Kobrin (1994), Kwantes and Chung-Yan (2012), Lill (2012), Mikhaylov and Fierro (2015), Nielsen (2014), Paul (2000), Pucik (2006) Human resources practise and organisational strategy…”
Section: Category Descriptionmentioning
confidence: 99%
“…Previously, [47] found that managers with international education have a higher level of international experience compared to overseas assignments alone. An international education provides managers with more knowledge and greater exposure of the dynamics in the international environment [2], [48]. [49] indicate that managers need international perspectives and exposure as early as possible to maximize the quality of their global mindset.…”
Section: International Education and Global Mindsetmentioning
confidence: 99%